Las infraestructuras aeroportuarias: tipo de propiedad y su relación con la eficiencia (2015)
Air transport has been characterized for being one of the fastest growing sectors. This significant growth is a challenge for airport infrastructures in terms of capacity and management. The shift to commercialization and privatization of airports has followed the same path of the deregulation and privatization of airlines, but with certain delayed. One of the common reasons for these new processes is the improvement in efficiency levels in order to face a highly competitive industry. This reflection paper focuses on a generalized idea that considers the form of a firm ownership and its management model is positively associated to high levels of productivity. Studies addressed in the present paper are limited to those papers considering DEA as the technique of efficiency analysis for being one of the most accepted in the academic literature.